2016
DOI: 10.1159/000438657
|View full text |Cite
|
Sign up to set email alerts
|

Beat Rate Variability in Murine Embryonic Stem Cell-Derived Cardiomyocytes: Effect of Antiarrhythmic Drugs

Abstract: Background/Aims: Heart rate variability (HRV) refers to the fluctuation of the time interval between consecutive heartbeats in humans. It has recently been discovered that cardiomyocytes derived from human embryonic and induced pluripotent stem cells show beat rate variability (BRV) that is similar to the HRV in humans. In the present study, clinical aspects of HRV were transferred to an in vitro model. The aims of the study were to explore the BRV in murine embryonic stem cell (mESC)-derived cardiomyocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
7
14
1
Order By: Relevance
“…By using mESC-derived CM in this study, we have revealed that the appearance of UCP3 in heart cannot be attributed to the establishment of electrical/contractile activity in CM, which is the main criterion for the successful mESC differentiation in all protocols ( Seiler and Spielmann, 2011 ; Niehoff et al, 2016 ). UCP3′s presence is rather an indicator of CM’ maturity, which includes (i) the presence of specific CM markers – SERCA2, TnC and GATA4 ( Figure 1C ), (ii) an increase of cristae density in mitochondria ( Figure 3C ), (iii) the appearance of lipid droplets (LD) and the establishment of multiple contacts between LD and mitochondria ( Figure 3D , arrows), and, the most important, (iv) a switch to FAO as a main type of cell metabolism ( Figure 4 and ( Lopaschuk and Jaswal, 2010 ; Mdaki et al, 2016 )).…”
Section: Discussionmentioning
confidence: 90%
“…By using mESC-derived CM in this study, we have revealed that the appearance of UCP3 in heart cannot be attributed to the establishment of electrical/contractile activity in CM, which is the main criterion for the successful mESC differentiation in all protocols ( Seiler and Spielmann, 2011 ; Niehoff et al, 2016 ). UCP3′s presence is rather an indicator of CM’ maturity, which includes (i) the presence of specific CM markers – SERCA2, TnC and GATA4 ( Figure 1C ), (ii) an increase of cristae density in mitochondria ( Figure 3C ), (iii) the appearance of lipid droplets (LD) and the establishment of multiple contacts between LD and mitochondria ( Figure 3D , arrows), and, the most important, (iv) a switch to FAO as a main type of cell metabolism ( Figure 4 and ( Lopaschuk and Jaswal, 2010 ; Mdaki et al, 2016 )).…”
Section: Discussionmentioning
confidence: 90%
“…For human pluripotent cells, embryoid body formation or other growth factors are essential for cardiomyocyte differentiation (Mummery et al, ). Murine or human ESC‐derived cardiomyocytes have already provided a promising source of material for cell therapy and drug screening (Zhang et al, ; Niehoff et al, ), so our rES‐like cells could be a source of material for heart disease and differentiation research.…”
Section: Discussionmentioning
confidence: 99%
“…The glass pipette was filled with the pipette solution (in mM): 120 KCl, 5 EGTA, 1 MgCl 2 , 5 Na2ATP, 10 HEPES, adjusted to pH = 7.4 with KOH. Experiments were performed at RT, as has been noted [31-33]. …”
Section: Methodsmentioning
confidence: 99%